The complement receptor C5aR2 regulates neutrophil activation and function contributing to neutrophil-driven epidermolysis bullosa acquisita - Seiler, Daniel L.; Kähler, Katja H.; Kleingarn, Marie; Sadik, Christian D.; Bieber, Katja; Köhl, Jörg; Ludwig, Ralf J.; Karsten, Christian M. (Frontiers in Immunology, 2023)
Introduction The function of the second receptor for the complement cleavage product C5a, C5aR2, is poorly understood and often neglected in the immunological context. Using mice with a global deficiency of C5aR2, we have previously reported an important role of this receptor in the pathogenesis of the neutrophil-driven autoimmune disease epidermolysis bullosa acquisita (EBA). Based on in vitro analyses, we hypothesized that the absence of C5aR2 specifically on neutrophils is the cause of the observed differences. Here, we report the generation of a new mouse line with a LysM-specific deficiency of C5aR2. Methods LysM-specific deletion of C5aR2 was achieved by crossing LysMcre mice with tdTomato-C5ar2fl/fl mice in which the tdTomato-C5ar2 gene is flanked by loxP sites. Passive EBA was induced by subcutaneous injection of rabbit anti-mouse collagen type VII IgG. The effects of targeted deletion of C5ar2 on C5a-induced effector functions of neutrophils were examined in in vitro assays. Results We confirm the successful deletion of C5aR2 at both the genetic and protein levels in neutrophils. The mice appeared healthy and the expression of C5aR1 in bone marrow and blood neutrophils was not negatively affected by LysM-specific deletion of C5aR2. Using the antibody transfer mouse model of EBA, we found that the absence of C5aR2 in LysM-positive cells resulted in an overall amelioration of disease progression, similar to what we had previously found in mice with global deficiency of C5aR2. Neutrophils lacking C5aR2 showed decreased activation after C5a stimulation and increased expression of the inhibitory Fcγ receptor FcγRIIb. Discussion Overall, with the data presented here, we confirm and extend our previous findings and show that C5aR2 in neutrophils regulates their activation and function in response to C5a by potentially affecting the expression of Fcγ receptors and CD11b. Thus, C5aR2 regulates the finely tuned interaction network between immune complexes, Fcγ receptors, CD11b, and C5aR1 that is important for neutrophil recruitment and sustained activation. This underscores the importance of C5aR2 in the pathogenesis of neutrophil-mediated autoimmune diseases.